A Case of Ertapenem Neurotoxicity Resulting in Vocal Tremor and Altered Mentation in a Dialysis Dependent Liver Transplant Patient - Ramy M. Hanna; Shih-Fan Sun; Pryce Gaynor (MDPI AG, 2018)
Carbapenem agents are advanced derivatives of cephalosporins that are active against bacteria that produce extended spectrum beta lactamases (ESBL). These antibiotics are resistant to enzymatic cleavage, and have good central nervous system penetration. Given this fact, it is not surprising that these drugs have been reported to cause neurological side effects like seizures and encephalopathy. We report a case of a patient on hemodialytic support who had a notable change in mentation and vocal tremor. This was at first attributed to calcineurin toxicity, but after the finding of a normal tacrolimus level, ertapenem neurotoxicity was suspected. After discontinuation of the offending agent, the patient’s vocal tremor, cognition, and neurological function returned to baseline levels.